Pengetahuan Siswa Remaja Tentang Bahaya Merokok di SMP Negeri 2 Rambah Hilir Kabupaten Rokan Hulu - Wulandari, Sri (Jurnal Martenity and Neonatal, 2017)
A cigarette containing hazardous chemical which is a a material that can lead to dependency psychical and can cause cancer .According to data from riskesdas riau the number of smokers increased that is in 2007 there are 9.6 % and in 2013 there are 18 % .The purpose of this study is to find picture students teenagers knowledge about danger of smoking in junior high schools 2 rambah hilir kabupaten rokan upstream .The kind of research in use is descriptive .Sample in this research were 143 people .A measuring instrument in this research was the questionnaire as many as 20 questions .The result of this research that is , of teenagers about danger of smoking shown the result that respondents knowledgeable good were 77 people (53.8%) , knowledgeable enough were 61 people (42.7 %) and knowledgeable less were 5 people (3.5 %) .Conclusion the result of this research is that overall level of teenagers about danger of smoking the majority knowledgeable good seban